Evaluating an online learning environment - Stacey, Elizabeth; Rice, Mary (Australasian Journal of Educational Technology, 2002)
This paper reports on an evaluation undertaken under the auspices of the cross-institutional CUTSD funded project which was established to facilitate evaluations of computer facilitated learning with an action inquiry model of evaluation (Phillips, 2002). Our evaluation focused on students' learning processes and outcomes in an online learning environment established for postgraduate education students studying an Open and Distance Education Specialism in a Masters program at Deakin University. Online conferencing has been progressively used in this specialism, and was an integral part of the program at the time of this study, which followed students studying online in five units. The units had computer conferences established with FirstClass software for electronic discussion of tasks and activities, with the aim of engaging students in learning interactively. Our participation in the CUTSD project resulted from the need to evaluate the extent to which students engaged in the conferencing environment, as intended by the learning design. It was also designed to evaluate the effectiveness of established practice with a view to modifying it in response to student feedback.